Natural Resource Management using Participatory Process of Youth Volunteer in Community - Klomkul, Lampong (International Journal of Psychosocial Rehabilitation, 2020)
The purposes of this research were to study the state of area, water and community potential, to develop and propose the method of natural resource management using participatory process of youth volunteer in community. Action research and quantitative research were used and research tools were interview form and questionnaires. Data were collected from in-depth interview, focus group discussion and quasi-experimental design. Qualitative data from 31 key informants was analyzed by using content analysis whereas quantitative data collected from 134 samples was analyzed by using descriptive statistics. Results indicated that the area and water in community has only one source of water, and it was not enough for utilization. They could not save the water during flooding season. Therefore, the leader of the community tried to find the best way to preserve water using technique of adding water to underground and making life dam in order to slow down water. Five steps of natural resource management process using participatory process of youth volunteer in community consisted of pre-research plan, planning, action plan, implementation, and follow up. Results of post-test and follow up showed higher score than pretest at significant level of .05.